General practitioner workload with 2,000 patients - Mills, K A (1986)
This study was designed to investigate the relationship between general practice workload, the number of partners in the practice, and the use of health centre premises. Thirty general practitioners in twelve randomly selected practices (each with a list size of 2,000 patients per doctor) agreed to record a week's work on pre-printed forms. Information was gathered on content of care in the surgery, number of non-surgery and indirect contacts and time spent on work activities. Content of care was influenced by whether or not the doctors were based in a health centre, rather on how many partners they had. Conversely the numbers of non-surgery and indirect contacts and the time spent on all work activities were more affected by the number of partners. Two factors — consultation rate and the rate at which doctors initiate consultations — were found to be independent of either of the two variables considered.